DOI: 10.11606/t.3.2012.tde-06062013-170116
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização de propriedades de papel para impressão por jato de tinta.

Abstract: Os métodos de análise tradicional não conseguem caracterizar os papéis em níveis de resolução capazes de fornecer informações sobre a influência das propriedades estudadas na impressão por jato de tinta. Ao mesmo tempo, a caracterização do papel para este tipo de impressão e a compreensão das influências das propriedades do papel no espalhamento e absorção de tinta e líquidos em geral só é possível quando as propriedades são analisadas em conjunto.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0
3

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 18 publications
1
2
0
3
Order By: Relevance
“…2C 1-6 ) showed higher dispersion of the SSK value À0.28 (AE0.34) and SKU > 3, Table 1, showing an irregular surface with extreme peaks and valleys. Yasumura et al 39 reported that the characterization of paper for printing showed SSK values of zÀ0.5 and SKU > 3 for the office-paper type, which were similar to those observed in this study. In addition, topographic images obtained in the authentic chalcographic region were markedly different from those in the counterfeit region.…”
Section: Vsc and Afmsupporting
confidence: 90%
See 1 more Smart Citation
“…2C 1-6 ) showed higher dispersion of the SSK value À0.28 (AE0.34) and SKU > 3, Table 1, showing an irregular surface with extreme peaks and valleys. Yasumura et al 39 reported that the characterization of paper for printing showed SSK values of zÀ0.5 and SKU > 3 for the office-paper type, which were similar to those observed in this study. In addition, topographic images obtained in the authentic chalcographic region were markedly different from those in the counterfeit region.…”
Section: Vsc and Afmsupporting
confidence: 90%
“…In general, when SSK y zero, it suggests a symmetrical data distribution or even around the median plane; when SSK s zero, an asymmetric distribution is suggested where a at surface with small peaks (SSK > 0) or small valleys (SSK < 0) can be observed. 39 SKU was determined by using eqn (2) of the WITec data evaluation soware and indicated whether data were arranged atly or sharply about the mean.…”
Section: Characterizationmentioning
confidence: 99%
“…Além destas, fibras sintéticas, minerais ou animais podem ser incorporadas ao papel dependendo de sua finalidade. A maior fonte de fibras para a produção de papel é, sem dúvida, a pasta celulósica proveniente de fibras de madeira (Yasumura, 2011). A celulose é o principal material estrutural da fibra, é um carboidrato que está presente em quase todos os vegetais e pertence ao grupo dos produtos naturais (Canevarolo, 2002).…”
Section: Papelunclassified
“…A celulose é importante para as características finais do papel devido à capacidade de atração entre as suas moléculas que é a principal fonte de ligações elementos, denominados elementos de vaso (Yasumura, 2011).…”
Section: Papelunclassified
See 1 more Smart Citation